CLIMA LABORAL EN LOS SERVIDORES PÚBLICOS DE LA UNIDAD EDUCATIVA VIRGILIO ABARCA MONTESINOS, PARROQUIA URDANETA, CANTÓN SARAGURO, PROVINCIA DE LOJA, AÑO 2024 - Cabrera Cabrera, Jefferson Rolando (2025)
The present research work entitled “Work Climate among Public Servants at the Virgilio Abarca Montesinos Educational Unit, Urdaneta Parish, Saraguro Canton, Loja Province, Year 2024” had as its general objective to determine the work climate among the public servants of such institution. To achieve this objective, a quantitative approach methodology was used, with a descriptive and cross-sectional design, employing methods such as analytical and deductive. Data collection was carried out through surveys applied to 33 public servants of the educational unit, evaluating 5 dimensions, which were obtained from the Guide for the Application of the Work Climate Evaluation Questionnaire. The results revealed that the public servants of the institution have a “Very good” level of work climate, with an overall score of 78.30 out of 100, indicating that it is above average. However, areas for improvement were identified, especially in dimensions such as recognition and communication, which scored lower compared to other evaluated dimensions. This analysis highlights the importance of a favorable work climate in the effectiveness of public servants and emphasizes the need to develop specific strategies to address the critical areas identified, in order to further improve the work environment and promote employee productivity and satisfaction. In conclusion, although the work climate is positive, the study points out the urgency of addressing the aspects that require attention to ensure an optimal and sustainable work environment.